2013
DOI: 10.1038/ejhg.2012.293
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis shows association of epigenetic changes in regulators of Rab and Rho GTPases with spinal muscular atrophy severity

Abstract: Spinal muscular atrophy (SMA) is a monogenic disorder that is subdivided into four different types and caused by survival motor neuron gene 1 (SMN1) deletion. Discordant cases of SMA suggest that there exist additional severity modifying factors, apart from the SMN2 gene copy number. Here we performed the first genome-wide methylation profiling of SMA patients and healthy individuals to study the association of DNA methylation status with the severity of the SMA phenotype. We identified strong significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…For example, the methylation of other genes, such as CHML, ARHGAP22, CYTSB, CDK2AP1, and SLC23A2, also contributes to the SMA phenotype modification (Zheleznyakova et al, 2013). SMA clinicopathology may also be affected by other epigenetic modifications such as acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the methylation of other genes, such as CHML, ARHGAP22, CYTSB, CDK2AP1, and SLC23A2, also contributes to the SMA phenotype modification (Zheleznyakova et al, 2013). SMA clinicopathology may also be affected by other epigenetic modifications such as acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the cascade of actin remod eling also suffers in SMA, a neurodegenerative disease in newborns and children [62]. Genome wide methy lation analysis in patients with SMA, as compared with healthy people, found significant differences in the level of methylation of CpG sites in 40 genes.…”
Section: Neuroepigenetics: Genetic Diseases and Syndromes With Multipmentioning
confidence: 98%
“…With the database String 9.05, it was found that the CHML gene product, REP2, interacts with Rab5A, Rab3A, RablA, and Rab6A GTPases and that the protein ARHGAP22 interacts with RhoB, RhoD, RhoF, RhoG, RhoH, RhoU, and RhoQ GTPases (string db.org, medium confidence score 0.400) [62].…”
Section: Neuroepigenetics: Genetic Diseases and Syndromes With Multipmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct DNA methylation patterns provide regulation of cell type-specific gene expression by affecting the capacity of DNA to interact with transcription factors and methyl-CpG-binding proteins (Doerfler 1981, Razin & Cedar 1991, Zou et al 2012). Numerous studies discuss the possible role of the altered DNA methylation patterns in the initiation and progression of various pathologies, including developmental failures (Shi & Haaf 2002, Pliushch et al 2010, Ehrlich & Lacey 2013, Shubina et al 2013, Skryabin et al 2013, Zheleznyakova et al 2013, Luo et al 2014, Pendina et al 2014.…”
Section: Introductionmentioning
confidence: 99%